Representation and Interpretation of Genetic Analysis: A Strategy of Development for the Personal Genetics Card Information System - Huptych, Michal; Lhotská, Lenka (Studies in health technology and informatics, 2020)
In this paper, we describe a strategy for the development of a genetic analysis comprehensive representation. The primary intention is to ensure the available utilization of genetic analysis results in clinical practice. The system is called Personnel Genetic Card (PGC), and it is developed in cooperation of CIIRC CTU in Prague and the Mediware company. Nowadays, genetic information is more and more part of medicine and life quality services (e.g. nutritional consulting). Therefore, there is necessary to bind genetic information with the clinical phenotype, such as drug metabolism or intolerance to various substances. We proposed a structured form of the record, where we utilize the LOINC® standard to identify genetic test parameters, and several terminology databases for representing specific genetic information (e.g. HGNC, NCBI RefSeq, NCBI dbNSP, HGVS). Further, there are also several knowledge databases (PharmGKB, SNPedia, ClinVar) that collect interpretation for genetic analysis results. In the results of this paper, we describe our idea in the structure and process perspective. The structural perspective includes the representation of the analysis record and its binding with the interpretations. The process perspective describes roles and activities within the PGC system use.
Keywords: osobní údaje; eHealth; Phenotype; databáze genetické; Databases, Genetic; fenotyp; Genetic Testing; genetic analysis; standards; genetické testování; Personally Identifiable Information; Logical Observation Identifiers Names and Codes; information system; terminology